Book Review: A Viewer and a Voyeur - Curnow, Trevor (Analytic Teaching, 2014)
Introduction:  Eulalia Bosch is well-known for her work in organising innovative exhibitions. Here, however, in addition to the role of organiser, she also plays those of eavesdropper and midwife. I send you this Cadmium Red is an exhibition as well as a book, and it is based, as the subtitle indicates, on a correspondence between John Berger, artist and writer, and John Christie, artist and film-maker. Eulalia was, in her own words, ‘an occasional witness’ to this correspondence, which began when John C sent John B a painted square of Cadmium Red. For the next two years or so all manner of items changed hands including colours, letters, poems and booklets. Cadmium Red gave way to Rust-Iron, blue, black, gold, green.... The subject of their correspondence was, in the words of Berger, ‘darkness, light, pages, colours, stones, bodies, layers.’ But above all, it was about colour. Each colour led to a series of reflections. Some were purely personal, based on subjective associations: but these were never more than a beginning. They led on to wideranging considerations of the meanings and natures of the different colours, drawing on personal experience and the history of art. Matisse and Mondrian, Kandinsky and Klee all find their way into the discussions. The authors’ own ideas are also regularly interspersed with those of others such as Yves Klein, Joseph Beuys and John Gage. In this way, the discussion unfolds into a prolonged meditation, not systematic but multi-faceted, on the notion and significance of colour itself.